Total productive maintenance: an in-depth review with a focus on overall equipment effectiveness measurement - Joyeshree Biswas (International Journal of Research in Industrial Engineering)
This paper will explore the objectives and advantages associated with the implementation of Total Productive Maintenance (TPM). It will specifically delve into the calculation of Overall Equipment Effectiveness (OEE) within a steel company based in Jordan. Furthermore, it will analyze the concept of the "big six losses" prevalent in various industries, encompassing factors such as quality, availability, and speed. A case study sourced from the electronics industry in Bangladesh will be presented, detailing observations collected over ten working days. During two months, multidisciplinary teams were assembled to assess the efficacy of collaboration between different departments in eliminating organizational silos and enhancing maintenance processes. Additionally, frontline workers on the production line were involved in adopting autonomous maintenance practices, contributing to daily maintenance operations. The outcome of this initiative revealed notable achievements, with the company attaining a 99% score in the quality factor of the OEE equation, 49% in availability, and 84% in performance. Recommendations for improvement were proposed, including the adoption of techniques such as Single Minute Exchange of Die (SMED), Computer Maintenance Management System (CMMS), and optimized production planning strategies. These suggestions aim to bolster maintenance procedures and enhance overall productivity within the industry.